2012
DOI: 10.1016/j.chroma.2012.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity screening of novel drug-like compounds and comparison to clogP

Abstract: We determined the distribution coefficients of solutes between a polymer film phase (polyvinyl chloride (PVC) with 67% (w/w) dioctyl sebacate (DOS)) and an aqueous phase in a 96-well format. The parallel measurement approach is efficient and uses very little material. Polymer-water distribution coefficients (Dpw) at different pH values yield the pKa and polymer-water partition coefficient values (Ppw) of the solutes. Log Ppw of a prominent drug-like compound, 2H-1, 2, 6-thiadiazine, 3-methyl-5-phenyl-, 1, 1-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…46), showing its good overall capability to penetrate the cell membrane. [35,36] All these test results clearly indicated that these structural modifications, which were inspired by our previous structure and activity relationship (SAR) explorations are rational and effective. Moreover, this study further confirmed the benefit of 1-substitutedacetamide linker in the C-2 aniline, and revealed that the morpholine substituent (6 a,c,d,h) in the C-2 aniline side chain of the pyrimidine core is more favorable than the piperazine ring (6 b,e,f,g) at the same position.…”
Section: Novel Pyrimidines As Multitarget Protein Tyrosine Kinase Inhmentioning
confidence: 68%
See 1 more Smart Citation
“…46), showing its good overall capability to penetrate the cell membrane. [35,36] All these test results clearly indicated that these structural modifications, which were inspired by our previous structure and activity relationship (SAR) explorations are rational and effective. Moreover, this study further confirmed the benefit of 1-substitutedacetamide linker in the C-2 aniline, and revealed that the morpholine substituent (6 a,c,d,h) in the C-2 aniline side chain of the pyrimidine core is more favorable than the piperazine ring (6 b,e,f,g) at the same position.…”
Section: Novel Pyrimidines As Multitarget Protein Tyrosine Kinase Inhmentioning
confidence: 68%
“…Moreover, compound 6 a has low toxicity against the normal human bronchial epithelioid (HBE) cells at concentration lower than 2.78 μM. In addition, compound 6 a displayed a moderate cLog P value (4.46), showing its good overall capability to penetrate the cell membrane …”
Section: Figurementioning
confidence: 99%
“…The log P and log D values—representing the partition and the distribution coefficients, respectively, of a compound between H 2 O and octan‐1‐ol—are widely used . A computational approach to calculating the intrinsic hydrophobicity of an amino acid residue in a peptide has also been established …”
Section: Introductionmentioning
confidence: 99%
“…It should be stressed that in some cases these relationships require corrections considering ionization of the analytes. 21,22 In recent years, several adsorbents imitating the biological membranes have been developed. The artificial biological membranes with immobilized phosphatidylcholine, ceramides, keratin, proved to be useful in drug design process, to compare lipophilicity, modeling bioavailability or anticipate the process of the cell membrane permeation.…”
mentioning
confidence: 99%